Environmental practices in frederico westphalen’s public schools - Zanatta, Tiago; Rosa, Magda; Santos, Juniara Valeria dos; Salamoni, Adriana Tourinho (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/2236117010740 Environmental education has the task to teach current and future generations the importance of the environment, being a learning process aimed at improving the quality of life where you learn to deal with the environment and respecting it himself. It is important to work with this theme in school, since this is the social space and the location where the student will sequence their socialization process. Associated with this, the activities in public institutions of higher education must be grounded in teaching, research and extension. As continuing education, outreach activities should match the processes of education, culture and science, to provide the results of scholarly activities, aimed at cooperation and integration between the institutions and the society where they are inserted, giving the possibility to participate in academic activities interdisciplinary, inserting it into the theme of society and preparing them for the labor market. The aim was to spread the concepts of environment, stimulating the students to take the steps necessary to protect it and improve it, making it the multiplier. The project was conducted with elementary students of public schools. It discussed issues related to the environment, conservation and/or restoration, sustainable use of resources, native forests, plantation forests and the most common species in the region. Scholars of Forestry have had the opportunity to show their knowledge in various disciplines of the course. It observed different responses of students to work methodology employed, depending on the school attended and year visited. It is intended to continue the work, visiting other schools in the city and neighborings.